Systematic review of cognitive development across childhood in Down syndrome: implications for treatment interventions. (12th March 2012) - Patterson, T.; Rapsey, C. M.; Glue, P.
Abstract Background There is conjecture regarding the profile of cognitive development over time in children with Down syndrome (DS). Characterising this profile would be valuable for the planning and assessment of intervention studies. Method A systematic search of the literature from 1990 to the present was conducted to identify longitudinal data on cognitive trajectories in children with DS. Results Thirteen studies were identified: six assessed overall cognitive performance and seven assessed specific cognitive domains. Studies assessing IQ reported a decline across time. Studies assessing change in cognitive domains were, for the most part, not interpretable because of large age ranges in samples obscuring age‐specific data. Conclusion The current literature has only begun to describe typical cognitive developmental trajectories in children with DS; additional research is needed to clarify this topic.